Chemical Constituents and Biological Activities of Curcuma Xanthorrhiza and Curcuma Heyneana - Abd Rashid, Nur Yuhasliza (2004)
Five compounds were isolated from Curcuma xanthorrhiza. The hexane extract afforded three pure compounds, which were identified as α- curcumene (21), germacrone (17) and zederone (66), while dichloromethane extract gave yellow powder product, which was characterized as curcumin (5) together with colourless oil, xanthorrhizol (16). The studies on Curcuma heyneana afforded four compounds. The hexane extract yielded oxycurcumenol epoxide (64), which is a new natural product, isocurcumenol (31) and curcumenol (32). In addition, dichloromethane extract produced stigmasterol (65).